Jia-Ji Electro-Acupuncture Improves Locomotor Function With Spinal Cord Injury by Regulation of Autophagy Flux and Inhibition of Necroptosis - Hongna, Yin; Hongzhao, Tian; Quan, Li; Delin, Feng; Guijun, Liu; Xiaolin, Lv; Fulin, Guan; Zhongren, Sun (Frontiers in Neuroscience, 2021)
Jia-Ji electro-acupuncture (EA) has been widely applied in clinic to exhibit curative effects on spinal cord injury (SCI). However, its underlying mechanisms leading to improvement of motor function after spinal cord injury remain unclear. Allen's method was made by NYU Impactor M-III equipment to create the spinal cord injury rats model. Rats were randomly divided into four groups: Sham (only laminectomy), Model (SCI group), EA (Jia-Ji EA treatment), EA+CQ (Jia-Ji EA + inhibitor chloroquine). Basso-Beattie-Bresnahan assessment showed improvement of hind limb motor function after Jia-Ji electro-acupuncture treatment. Histological change of injured spinal cord tissue was alleviated after treatment, observed by hematoxylin-eosin and Nissl staining. The mRNA and protein expression levels of RIPK1, RIPK3 and MLKL were decreased in EA group. Besides, the increased expression of LC3 and reduced expression of P62 after treatment compared with Model group, confirmed that Jia-Ji electro-acupuncture could enhance the autophagy flux. Electron microscopy imaging showed increasing the number of lysosomes, autophagosomes and autolysosomes after Jia-Ji electro-acupuncture treatment. Furthermore, inhibition of lysosome function with CQ led to partly eliminate the effect of EA on reducing necroptosis. These data make the case that Jia-Ji electro-acupuncture treatment may improve limb motor function by promoting autophagy flux and inhibiting necroptosis.